Heterosis in COMT Val158Met Polymorphism Contributes to Sex-Differences in Children’s Math Anxiety - Júlio-Costa, Annelise; Martins, Aline Aparecida Silva; Wood, Guilherme; Almeida, Máira Pedroso de; Miranda, Marlene de; Haase, Vitor Geraldi; Carvalho, Maria Raquel Santos (Frontiers in Psychology, 2019)
Math anxiety (MA) is a phobic reaction to math activities, potentially impairing math achievement. Higher frequency of MA in females is explainable by the interaction between genetic and environmental factors. The molecular-genetic basis of MA has not been investigated. The COMT Val158Met polymorphism, which affects dopamine levels in the prefrontal cortex, has been associated with anxiety manifestations. The valine allele is associated with lower, and the methionine allele with higher, dopamine availability. In the present study, the effects of sex and COMT Val158Met genotypes on MA were investigated: 389 school children aged 7 to 12 years were assessed for intelligence, numerical estimation, arithmetic achievement and MA and genotyped for COMT Val158Met polymorphism. The Math Anxiety Questionnaire (MAQ) was used to assess the cognitive and affective components of MA. All genotype groups of boys and girls were comparable regarding genotype frequency, age, school grade, numerical estimation, and arithmetic abilities. We compared the results of all possible genetic models: codominance (Val/Val vs. Val/Met vs. Met/Met), heterosis (Val/Met vs. Val/Val plus Met/Met), valine dominance (Val/Val plus Val/Met vs. Met/Met), and methionine dominance (Met/Met plus Val/Met vs. Val/Val). Models were compared using AIC and AIC weights. No significant differences between girls and boys and no effects of the COMT Val158Met polymorphism on numerical estimation and arithmetic achievement were observed. Sex by genotype effects were significant for intelligence and MA. Intelligence scores were higher in Met/Met girls than in girls with at least one valine allele (valine dominance model). The best fitting model for MA was heterosis. In Anxiety Toward Mathematics, heterozygous individuals presented MA levels close to the grand average regardless of sex. Homozygous boys were significantly less and homozygous girls significantly more math anxious. Heterosis has been seldom explored, but in recent years has emerged as the best genetic model for some phenotypes associated with the COMT Val158Met polymorphism. This is the first study to investigate the genetic-molecular basis of MA.